An improved vigener algorithm based on circular-left-shift key and MSB binary for data security - Aso Ahmed Majeed; Banaz Anwer Qader (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Cryptography is a significant study area at present since it can be vital to protect exceedingly sensitive and secret information from illegal fraud during network transmission. One of the basic cryptographic algorithms is the Vigenere cipher, which is a very easy encryption method to be used as an alternative to Caesar cipher for encrypting the text of the message. In this paper, we enhance the Vigenere algorithm and propose a new method by shifting the key in each message to prevent repeating the messages. Also, it converts the messages into binary form rather than an alphabet. Furthermore, it adds a few bits of random padding to each block of outputs to send a series of bits. The proposed algorithm is named “Circular-Left-Shift Key-based Vigener Algorithm using MSB Binary (CLS-V-MSB)”. Finally, this technique slightly raises the size of the ciphertext, but substantially increases the cipher's protection, achieves the security objectives (authentication, confidentiality, integrity, freshness, and non-repudiation), and avoids Kasiski and Friedman.